ANALISIS PENDAPATAN ASLI DAERAH TERHADAP KEMANDIRIAN DAERAH KOTA SAMARINDA TAHUN 2005-2011 - Huda, Nurul (EKONOMIA, 2012)
Kalimantan province is eager to help to finance the construction of the development, the local government tried to boost the source of local revenue as a manifestation of a real implementation of regional autonomy and responsible. In the implementation of regional autonomy in demand for government institutions have greater financial independence, attempts to measure the degree of independence is to compare the magnitude of the realization of the region with total revenue. Problems in this study is how the level of independence samarinda city government in 2005 – 2011.The purpose of this study to determine how the realization of revenue and asset management services in the areas of financial year 2005 to 2011.Based on the analysis and discussion, it can be seen from the calculations and the discussion concluded that the level of independence of the local financial income of financial and asset management services in the city samarinda 2005 -2011 respectively 8.16%, 5.99%, 6.09%, 5.62%, 9.23%, 8.40% and 9.12%, and these values indicate that the degree of independence is still considered very low. Effective in revenue conclude that the ability of local governments to achieve acceptance of PAD compared to the targeted interval in 2005 amounted to 101%, in 2006 by 95%, in 2007 by 110%, in 2008 by 98%, in the year 2009 amounted to 101%, in 2010 by 84% and in 2011 by 103% and values is the ability of local governments to create effective classified PAD.